The future sustainability of Malaysian higher education institutions: what matters most? - Mohd Ali, Hairuddin; Lasisi, Abass Ayodele; Ibrahim, Mohd Burhan (USM, 2019)
The purpose of the study was to examine the relationship between the organisational quality management initiatives (OQMI) and organisational culture (OC) on the sustainability of Malaysian higher education institutions (SMHEI). The study utilised 263 top administrators’ completed questionnaire survey from universities in Peninsular Malaysia. The statistical techniques employed in this study were descriptive statistics, confirmatory factor analysis (CFA), and a full-fledged structural equation modelling to address the research questions and hypotheses testing. The findings revealed that long-term strategic planning initiatives (LSPI) required a thorough revision; communication and decision-making, and organisational climate of Malaysian higher education institutions (MHEI) persisted as challenges in improving the SMHEI. It was also revealed that the implementation of balanced scorecard could enhance the effectiveness and efficiency of MHEI. This study provides a basis for future studies, particularly in the Peninsular Malaysia context. Theoretically, the study also found that not only leadership perspectives required further investigation but also the financial, customer, internal process, and learning and growth perspectives in the administration for SMHEI. Keywords: balanced scorecard, sustainability, organisational climate, quality assurance, long-term strategic planning initiatives